Exploring the effects of Gastrodia elata Blume on the treatment of cerebral ischemia-reperfusion injury using UPLC-Q/TOF-MS-based plasma metabolomics. Issue 11 (14th October 2019) - Wang, Dongxu; Wang, Qi; Chen, Renhao; Yang, Shinlin; Li, Zhifeng; Feng, Yulin
Abstract : This study was designed to investigate the protective effect of Gastrodia elata in rats with cerebral ischemia-reperfusion injury by a UPLC-Q/TOF-MS-based plasma metabolomics study. Abstract : Gastrodia elata Blume (Orchidaceae, GEB) is a medicinal plant that has been widely used in the treatment of cerebrovascular disease. This study explored the protective effects of GEB against cerebral ischemia-reperfusion using Information-Dependent Acquisition (IDA)-mediated UPLC-Q/TOF-MS-based plasma metabolomics. Cerebral ischemia-reperfusion (IR) injury was induced in male Wistar rats using the Zea Longa method. Biochemical and histological assays were performed to evaluate the therapeutic effects of GEB on IR rats. We found that the neurobehavioral scores and infarction areas of GEB and nimodipine treated groups were dramatically lower than those of the IR groups. Hematoxylin and Eosin (HE) staining and TdT-mediated dUTP Nick-End Labeling (TUNEL) showed that GEB significantly improved neuronal injury and prevented neuronal apoptosis. Biochemical analysis revealed that GEB prevented cerebral ischemia-reperfusion injury by regulating inflammation and oxidative injury. Through ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry-metabolomics-based approaches, 43 plasma metabolites related to GEB treatment were detected, 6 of which significantly differed ( p < 0.05) between the model and GEB groups. The levels of l -histidine, sphinganine, thymine, spermidine and deoxycytidine in the IR group were significantly higher than those in the sham group, but decreased following GEB treatment. Arachidonic acid levels were lower in the IR group, but dramatically increased in response to GEB. Pharmacodynamics and metabolomics confirmed that the mechanism of GEB in the treatment of cerebral ischemia was not only related to the reduction of inflammation, oxidation, neurotoxicity, and apoptosis, but also mediated through arachidonic acid metabolism, histidine metabolism, pyrimidine metabolism, arginine and proline metabolism, sphingolipid metabolism, and glycerophospholipid metabolism in vivo .